2018
DOI: 10.1186/s12931-018-0869-x
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of human neutrophil peptides in a mouse model of pneumonia and ventilator-induced lung injury

Abstract: BackgroundPneumonia is a major cause of high morbidity and mortality in critically illness, and frequently requires support with mechanical ventilation. The latter can lead to ventilator-induced lung injury characterized by neutrophil infiltration. The cationic human neutrophil peptides (HNP) stored in neutrophils can kill microorganisms, but excessive amount of HNP released during phagocytosis may contribute to inflammatory responses and worsen lung injury. Based on our previous work, we hypothesized that blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…Hasan et al suggested that desensitization of P2Y 2 and P2X 4 receptors might contribute to the development of VILI [ 95 ]. Zheng et al presented results that in a two-hit mouse model of Pseudomonas aeruginosa pneumonia with high-pressure ventilation a specific P2Y 6 receptor antagonist partially attenuated inflammation and lung injury without interfering with the ability of the immune system to clear the bacteria [ 215 ].…”
Section: The Role Of P2 Receptors In Lung Diseasementioning
confidence: 99%
“…Hasan et al suggested that desensitization of P2Y 2 and P2X 4 receptors might contribute to the development of VILI [ 95 ]. Zheng et al presented results that in a two-hit mouse model of Pseudomonas aeruginosa pneumonia with high-pressure ventilation a specific P2Y 6 receptor antagonist partially attenuated inflammation and lung injury without interfering with the ability of the immune system to clear the bacteria [ 215 ].…”
Section: The Role Of P2 Receptors In Lung Diseasementioning
confidence: 99%
“…We observed that HNP exerted microbicidal properties in clearing P. aeruginosa per se, while also increasing the P. aeruginosa -induced inflammatory response by enhancing IL-8 production in human lung epithelial cells. Since the use of the P2Y 6 antagonist MRS2578 attenuated the HNP-induced IL-8 production and did not affect the microbicidal activity of HNP, our results indicated that 1) HNPs acted on eukaryotic cells through ligand-receptor mechanisms1214 and kill prokaryotic cells via different approaches such as charge–charge interaction;32 and 2) the ligand-receptor mechanism seemed to override that of charge interaction when eukaryotic and prokaryotic cells were co-existent.…”
Section: Discussionmentioning
confidence: 77%
“…Levels of HNP are significantly elevated in the blood and body fluid including bronchoalveolar lavage fluid (BALF) and pleural fluid from patients with infections10 and ARDS 6,11. HNP has also been recently shown to act as an immunoregulatory agent due to its ability to induce cytokine production and to activate immune cells through mechanisms of ligand-receptor (i.e., the purinergic receptor P2Y 6 ) interaction 1214. Thus HNP is not only an important biomarker for infection but also an effector contributing to inflammation in lung microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…The P2Y6 receptor, in turn, was investigated in an animal model in the context of complicated bacterial pneumonia ( Pseudomonas aeruginosa ) and ventilator-induced lung injury [ 31 ]. In patients with COVID-19, there is an inflammatory infiltrate with neutrophils and the application of ventilators is common in severe cases of SARS [ 5 ].…”
Section: Possible Functions Performed By P2y2r and P2y6r In The Immunmentioning
confidence: 99%
“…In patients with COVID-19, there is an inflammatory infiltrate with neutrophils and the application of ventilators is common in severe cases of SARS [ 5 ]. In this research conducted by Zheng et al [ 31 ] on P2Y6R, there was an increment in the α-defensins released by neutrophils, which can kill microorganisms, but in excess contributes to the inflammatory response with high levels of cytokines (IL-1β, IL-6, and TNF-α) and injury to the epithelium and pulmonary endothelium. The intervention occurred through the use of MRS2578, a selective P2Y6R inhibitor, which attenuated the inflammatory state without affecting the anti-bacterial properties of α-defensins.…”
Section: Possible Functions Performed By P2y2r and P2y6r In The Immunmentioning
confidence: 99%